Prolactin protects hippocampal neurons against H2O2-induced neurotoxicity by suppressing BAX and NOX4 via the NF-κB signaling pathway. - Fernando Macías; Miriam Ulloa; Carmen Clapp; Gonzalo Martínez de la Escalera; Edith Arnold (PLoS ONE)
Reactive oxygen species (ROS) are physiological byproducts of neuronal metabolism. However, an imbalance between ROS generation and antioxidant capacity, often driven by dysregulated pro-oxidant enzymes like nicotinamide adenine dinucleotide phosphate oxidases (NOX), can result in deleterious oxidative stress. This oxidative stress is a critical factor in the pathogenesis of neurodegenerative diseases. While interventions with broad-spectrum antioxidants have demonstrated limited efficacy, the modulation of endogenous antioxidant mechanisms presents a promising therapeutic avenue. Here, we investigated the potential of the neuroprotective hormone prolactin to mitigate oxidative stress and subsequent neuronal cell death. Prolactin protected primary mouse hippocampal neurons from hydrogen peroxide (H2O2)-induced oxidative damage. Prolactin reduced ROS levels, lipid peroxidation, and apoptosis, and its effects were occluded by a specific prolactin receptor antagonist (G129R-hPRL). Mechanistically, prolactin suppressed H2O2-induced mRNA upregulation of pro-oxidative Nox4 and pro-apoptotic Bax. Moreover, prolactin induced nuclear factor kappa B (NF-κB) nuclear translocation, and the inhibition of the NF-κB signaling pathway abolished the neuroprotective and transcriptional effects of prolactin, indicating its central role in prolactin-mediated protection. Our findings indicate that prolactin exerts potent antioxidant and neuroprotective effects by modulating the expression of Nox4 and Bax, thereby reducing ROS generation and neuronal apoptosis. This study underscores the therapeutic potential of prolactin in attenuating oxidative stress and suggests a possible role in the treatment of neurodegenerative diseases.